2015
DOI: 10.1002/bies.201400174
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Breakage Model of genome architecture, reshuffling and evolution

Abstract: Our understanding of genomic reorganization, the mechanics of genomic transmission to offspring during germ line formation, and how these structural changes contribute to the speciation process, and genetic disease is far from complete. Earlier attempts to understand the mechanism(s) and constraints that govern genome remodeling suffered from being too narrowly focused, and failed to provide a unified and encompassing view of how genomes are organized and regulated inside cells. Here, we propose a new multidis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 123 publications
2
59
0
Order By: Relevance
“…However, this sort of restructuring of TADs appears to be rare during evolution, as TADs tend to overlap with highly syntenic genomic blocks of conserved enhancers and non-coding elements (Harmston et al, 2016). Interestingly, structural rearrangements between mammalian genomes appear to instead occur between the boundaries of adjacent domains (Farré et al, 2015)(Vietri Rudan et al, 2015b) (Figure 4Ai-ii). …”
Section: Introductionmentioning
confidence: 99%
“…However, this sort of restructuring of TADs appears to be rare during evolution, as TADs tend to overlap with highly syntenic genomic blocks of conserved enhancers and non-coding elements (Harmston et al, 2016). Interestingly, structural rearrangements between mammalian genomes appear to instead occur between the boundaries of adjacent domains (Farré et al, 2015)(Vietri Rudan et al, 2015b) (Figure 4Ai-ii). …”
Section: Introductionmentioning
confidence: 99%
“…2015), adaptive evolution (Ge et al. 2013), and the evolution of genome architecture (Farré et al. 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, discussions have been focussed on whether genome reshuffling act as barriers to gene flow (Rieseberg 2001; Navarro and Barton 2003; Faria and Navarro 2010; Farré et al 2013) or by modifying both the structure and regulation of genes located at, or near, the affected regions (Murphy et al 2005; Larkin et al 2009; Ullastres et al 2014). The main motivation behind these studies has been to find evidence of the adaptive value of genome reshuffling and of the mechanisms of its formation during mammalian diversification [reviewed in Farré et al (2015)]. …”
Section: Introductionmentioning
confidence: 99%
“…However, given the diversity of repetitive elements found in EBRs it is likely that sequence composition is not alone in influencing genome instability during evolution. In fact, the genomic distribution of mammalian EBRs can be considered a multifactorial affair, involving repetitive elements, functional constrains and changes in the chromatin state (Farré et al 2015). It was initially reported that EBRs are located in gene-rich regions (Murphy et al 2005; Lemaitre et al 2009), among others, those containing gene functional process networks, such as genes related to the immune system (Groenen et al 2012; Ullastres et al 2014).…”
Section: Introductionmentioning
confidence: 99%